Validasi Metode Penentuan Kadar Asam Klorogenat dan Kafein secara Simultan pada Serbuk Daun Kopi Robusta (Coffea Canephora) dengan Metode KLT Densitometri - Putri Aditama, Tiara Sagita; Kristiningrum, Nia; Wulandari, Lestyo; Holidah, Diana; Alishlah, Tanfidz; Puspitasari, Endah (Journal of Agropharmacy, 2025)
Coffee contains bioactive compounds such as chlorogenic acid and caffeine. Chlorogenic acid is recognized as a natural antioxidant, while caffeine is widely used to reduce fatigue and drowsiness. This study aims to simultaneously determine the content of chlorogenic acid and caffeine in robusta coffee leaf powder (Coffea canephora) using Thin Layer Chromatography (TLC) densitometry. The study identified an optimal eluent composition of ethyl acetate:formic acid:distilled water (18:1:1), with maximum wavelengths of 330 nm for chlorogenic acid and 274 nm for caffeine. High linearity was demonstrated with correlation coefficients of 0.993 for chlorogenic acid and 0.994 for caffeine. Sensitivity was validated with LOD values of 100.664 ng for chlorogenic acid and 297.232 ng for caffeine, and LOQ values of 301.994 ng for chlorogenic acid and 891.697 ng for caffeine. Selectivity was confirmed as the method effectively separated chlorogenic acid, caffeine, and other compounds with a resolution (Rs) ≥ 1.5, while specificity was evidenced through purity and identity values exceeding 0.99. Precision was proven through repeatability (%RSD for chlorogenic acid: 2.94%; caffeine: 2.27%) and intermediate precision (%RSD for chlorogenic acid: 2.26%; caffeine: 2.18%). Accuracy was achieved with mean recovery rates of 102.22% for chlorogenic acid and 99.73% for caffeine. The determination of chlorogenic acid and caffeine concentrations in robusta coffee leaf powder revealed variations between samples: PTPN XII Renteng yielded 2.278% ± 0.209% for chlorogenic acid and 1.171% ± 0.821% for caffeine, while Puslitkoka Indonesia samples showed 1.238% ± 0.206% for chlorogenic acid and 0.917% ± 0.823% for caffeine. Based on validation parameter assessments, the method is deemed valid as it meets all acceptance criteria for each parameter. This research provides an efficient and accurate analytical approach for simultaneous determination of bioactive compounds in robusta coffee leaves.